Paraguay : Fifth Review Under the Stand-By Arrangement and Request for Waiver of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Paraguay's Fifth Review Under the Stand-By Arrangement and Request for Waiver of Performance Criteria are discussed. The overall fiscal position remains in surplus, the exchange rate weakened slightly with respect to the U.S. dollar, but considerably with respect to the Brazilian real, and international reserves continue to rise. There have been delays in implementing the structural reform agenda. The authorities need to maintain momentum and deepen the structural agenda to reduce vulnerabilities, strengthen institutions, and lay the basis for growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet